A solar optical reflection lighting system for threshold zone of short tunnels: Theory and practice. (January 2023) - Yu, Shanchuan; Shi, Lingna (Serena); Zhang, Long; Liu, Zhenyi; Tu, Yun
Highlights: A novel solar optical reflection lighting system is designed for threshold zone of short tunnels. A sunlight ray-tracing simulation was performed to evaluate the illumination performance. Energy-saving of the system achieves more sustainable tunnel lighting in threshold zone. Abstract: This study develops a novel solar optical reflection (SOR) lighting system for threshold zone of short tunnels. In the system, the solar collector consists of a Fresnel lens and a dual axis sensor-date-time combined solar tracker, then the collected sunlight is reflected by a parabolic reflector and projected into the tunnel by air. In addition, a sunlight ray-tracing simulation was performed in TRACEPRO to evaluate the road surface illuminance distribution and illumination efficiency where the impacts of relative positions of system and projected light spot were investigated. Finally, the effectiveness and cost-benefit of the SOR lighting system were analyzed in the real tunnel application. The result shows that for an individual SOR lighting system, the illumination efficiency is relatively high, almost remaining the level of 70% theoretically. Upward projection of light spot leads to greater uniformity of illuminance distribution on the road surface, while it has lower average illuminance than downward projection. For array of multiple SOR lighting systems, downward projection outperforms upward projection with identical number of SOR lighting systems. In the real tunnel application, when the required illuminance and uniformity for threshold zone is met, the energy-saving of SOR lighting systems makes the tunnel lighting more sustainable compared with photoelectric tunnel lighting.